Associations between health literacy and preventive health behaviors among older adults: findings from the health and retirement study. (December 2016) - Fernandez, Dena; Larson, Janet; Zikmund-Fisher, Brian
Abstract Background While the association between inadequate health literacy and adverse health outcomes has been well documented, less is known about the impact of health literacy on health perceptions, such as perceptions of control over health, and preventive health behaviors. Methods We identified a subsample of participants (N = 707) from the Health and Retirement Study (HRS), a nationally representative sample of older adults, who participated in health literacy testing. Self-reported health literacy was measured with a literacy screening question, and objective health literacy with a summed score of items from the Test of Functional Health Literacy. We compared answers on these items to those related to participation in health behaviors such as cancer screening, exercise, and tobacco use, as well as self-referencing health beliefs. Results In logistic regression models adjusted for gender, education, race, and age, participants with adequate self-reported health literacy (compared to poorer levels of health literacy) had greater odds of participation in mammography within the last 2 years (Odds ratio [OR] = 2.215, p = 0.01) and participation in moderate exercise two or more times per week (OR = 1.512, p = 0.03). Participants with adequate objective health literacy had reduced odds of participation in monthly breast self-exams (OR = 0.369, p = 0.004) and reduced odds of current tobacco use (OR = 0.456, p = 0.03). In adjusted linear regression analyses, self-reported health literacy made a small but significant contribution to explaining perceived control of health (β 0.151, p = <0.001) and perceived social standing (β 0.112, p = 0.002). Conclusion In a subsample of older adult participants of the HRS, measures of health literacy were positively related to several health promoting behaviors and health-related beliefs and non-use of breast self-exams, a screening behavior of questionable benefit. These relationships varied however, between self-reported and objectively-measured health literacy. Further investigation into the specific mechanisms that lead higher literacy people to pursue health promoting actions appears clearly warranted.